Недоліки випробувань зчеплення арматури та пінобетону на розривній машині та шляхи їх усунення - Верба, Володимир; Янко, Андрій (Видавництво Національного університету «Львівська політехніка», 2009)
This article is devoted to the problems of laboratory experimental examination of adherence between aerated concrete and reinforcing steel bars caused by the usage of out-of-date tearing machines. The article points out the imperfections of such tests and gives the way of their elimination.
Keywords: розривна машина; недоліки; tearing machine; foam concrete; reinforcement bonding; measurement of bonding strength